Homocysteine and Hypertension in Diabetes: Does PPARγ Have a Regulatory Role? - Utpal Sen; Suresh C. Tyagi (PPAR Research)
Dysfunction of macro- and microvessels is a major cause of morbidity and mortality in patients with cardio-renovascular diseases such as atherosclerosis, hypertension, and diabetes. Renal failure and impairment of renal function due to vasoconstriction of the glomerular arteriole in diabetic nephropathy leads to renal volume retention and increase in plasma homocysteine level. Homocysteine, which is a nonprotein amino acid, at elevated levels is an independent cardio-renovascular risk factor. Homocysteine induces oxidative injury of vascular endothelial cells, involved in matrix remodeling through modulation of the matrix metalloproteinase (MMP)/tissue inhibitor of metalloproteinase (TIMP) axis, and increased formation and accumulation of extracellular matrix protein, such as collagen. In heart this leads to increased endothelial-myocyte uncoupling resulting in diastolic dysfunction and hypertension. In the kidney, increased matrix accumulation in the glomerulus causes glomerulosclerosis resulting in hypofiltration, increased renal volume retention, and hypertension. PPARγ agonist reduces tissue homocysteine levels and is reported to ameliorate homocysteine-induced deleterious vascular effects in diabetes. This review, in light of current information, focuses on the beneficial effects of PPARγ agonist in homocysteine-associated hypertension and vascular remodeling in diabetes.